Phytoremediating potential of the chicura (Ambrosia ambrosioides) in soils contaminated by heavy metals - Ramírez Gottfried, Ricardo Israel; García Carrillo, Mario; Alvares, Vicente de Paul; González Cervantes, Guillermo; Hernández Hernández, Vicente (Revista Mexicana de Ciencias Agrícolas, 2019)
The objective of the present research work was to evaluate the phytoremediation potential of Ambrosia ambrosioides soil, determine the absorption of heavy metals (cadmium, copper and lead) in the plant under different concentrations 0, 20, 40, and 60 mg L-1 applied in the irrigation water The analyzes were performed by atomic absorption, and with the data obtained the translocation factor and bioconcentration factor were calculated. The development of the experiment and laboratory analysis were performed at the Autonomous Agrarian University Antonio Narro Laguna Unit in the year 2018. A 3-by-4 factorial design with 4 repetitions was used, with factor A being heavy metal and B being the concentration of metal, 12 treatments were taken in total. The results showed that in root, stem and leaf the higher concentrations occurred in the treatment of copper at 20 mg L1 with values of 15 827.2, 13 030.9 and 4 979.4 mg kg-1 respectively. Copper was the metal that more absorbed the plant followed by cadmium and lead. The biological translocation factor indicated that cadmium is an element that the plant translocates towards its leaves more easily followed by copper. In Ambrosia ambrosioides the translocation of lead is null. The bioconcentration factor exceeded the comparative value of 1 in all treatments, this indicates that high phytoextraction was performed and that Ambrosia ambrosioides can be used in phytoremediation and soil health.
Keywords: absorption; accumulation; bioconcentration; translocation